Analysis of English Language Policy and Curriculum Implementation in Indonesia - Arip Hertanto; Budi Purwoko; Mufarrihul Hazin (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This conceptual article provides a synthesized analysis of Indonesia's English Language Policy (ELP) and its implementation over the last decade (2013-2023), building upon prior scholarship and extending to the recent Merdeka Curriculum. By drawing on existing research, policy documents, and evaluations of English Language Teaching (ELT), this study conceptualizes key trends, persistent challenges, and evolving strategies within Indonesia's English education landscape. It examines the interplay between national language policies, curriculum shifts, pedagogical innovations, and the practical realities of ELT across diverse Indonesian contexts. The analysis critically evaluates the conceptual underpinnings of policies aimed at fostering global citizenship and intercultural competence through English. It also addresses systemic implementation issues such as teacher preparedness, resource disparities (urban-rural), and the need for standardized assessment frameworks, which currently hinder the intended student-centered approach of the Merdeka Curriculum. Conceptually, this synthesis highlights a discernible gap between policy design and practical application. It identifies critical areas demanding attention, including enhancing teacher capacity to align with the Merdeka Curriculum, ensuring equitable resource distribution, and establishing robust assessment mechanisms. Framed within stages of policy analysis, the article suggests that while policy formulation has progressed, a deeper conceptual understanding and more effective strategies for implementation and evaluation are crucial. Ultimately, this conceptual synthesis underscores the necessity for a more nuanced and conceptually sound approach to policy implementation and evaluation to achieve the ELP's objectives of equitable and high-quality English language education in Indonesia. The article also proposes key conceptual considerations for future policy development and research directions, including longitudinal studies, comparative analyses, and innovations in teacher professional development.